The gendered politics of urban transformation: Gentrification and women’s survival spaces in Muara Teluk Naga - Megawati Rusdianto; Jely Agra Famela; Rini Naibaho; Alexander Silaen (Program Pascasarjana Universitas Negeri Yogyakarta, 2026)
This study analyzes the impact of gentrification on women in Muara Teluk Naga Village, Pantai Indah Kapuk (PIK), Tangerang. This study focuses on how the gentrification process exacerbates the feminization of poverty and marginalizes women from access to urban space. Using Kimberlé Crenshaw's concept of intersectionality, this study explores the multiple forms of oppression experienced by women because of forced displacement, rising living costs, and spatial changes triggered by large-scale development. Specifically, this study shows how women lose access to informal jobs, public services, and reproductive social spaces such as women's association activities, which previously supported their daily lives. The method used is a qualitative approach with a case study, through in-depth interviews and field observations. The results of the study show that gentrification strengthens gender-based structural inequalities, increases women's domestic burdens, and eliminates social spaces that are essential for women's survival in Muara Teluk Naga Village, PIK.